Some Medicinal Plants with Anti-breast Cancer Activity and the Input of Phytotherapy in the Treatment of Breast Cancer - Anago, Afiwa Dodzi; Gaetan Segbo, Julien A.; Gnangnon, Freddy; Akpovi, Casimir D.; Agbangla, Clement (European Scientific Journal, ESJ, 2023)
Aim: Breast cancer is the most commonly diagnosed cancer leading to death among women worldwide. Despite the advances in the diagnosis skills and in the treatment of breast cancer, it has been observed that the recurrence rate experienced by breast cancer patients is quite high. Many plants have been reported to have anti-breast cancer properties. This paper focuses on determining the role of phytotherapy in the treatment of breast cancer. Methods: The following key search terms were used on Pubmed, Google scholar, and Researchgate: breast cancer, breast cancer cell lines, phytotherapy, medicinal plants in the treatment of breast cancer, treatment of breast cancer, cytotoxics effects of plant extracts on breast cancer in vitro/ in vivo, integrative oncology, and natural products as sources of drugs. Pertinent reviews in English language were examined. Results: It has been observed that many studies were conducted in vitro and in vivo to demonstrate the anti-breast cancer activities of a myriad of plants. While investigations are being made to prove the anti-breast cancer effects of many plants, the use of phytomedicine is not generating enough attention by mainstream practitioners. Some significant results were observed by patients with breast cancer history through the combination of phytotherapy and conventional medicines. Discussion: The conventional treatment of breast cancer is often accompanied with side effects. Many patients in low-income countries are faced off with the enormous cost of conventional treatment. Hence, there is a need to search for new bioactive substances in the treatments of breast cancer. Phytotherapy is a promising approach and herbal preparations are to be used in the same way as conventional medicine in the treatment of breast cancer. Conclusion: Phytotherapeutics products are used more often in the treatment of breast cancer as adjuvant therapy. In Africa, the use of herbal products in the treatment of breast cancer still remains in the hands of traditional-practitioners, without any control of quality and efficacy. Standard methods for the preparation of herbal products are to be determined in order to adopt phytotherapy in the treatment of breast cancer as much as conventional treatment.